A flexible fiber-shaped supercapacitor utilizing hierarchical NiCo2O4@polypyrrole core–shell nanowires on hemp-derived carbon1. Issue 33 (7th September 2015) - Xiong, Wei; Hu, Xuan; Wu, Xu; Zeng, Yan; Wang, Bo; He, Guanhong; Zhu, Zhihong
<x xml:space="preserve">Abstract</x> A flexible supercapacitor is assembled based on NiCo2O4@polypyrrole core–shell nanowires on hemp-derived carbon and the as-synthesized electrode exhibits outstanding electrochemical performance and mechanical stability.